Law and Kingship in Thailand During the Reign of King Chulalongkorn - Engel, David (Michigan Papers On South And Southeast Asia, 2020)
This essay originated in an attempt to bring together the study of law and Thai history in a description of the transformation of Thailand during the late nineteenth and early twentieth centuries as seen from a legal point of view. The resulting work is based for the most part upon those royal enactments from 1873 to 1910 which seemed most crucially to affect the executive, legislative, and judicial functions of the king and the rights of private citizens. [ix]